COMPARATIVE ANALYSIS OF EMPLOYEE ENGAGEMENT BETWEEN CROSS GENERATION EMPLOYEES - Emilia, Sindi Budi (Jurnal Manajemen, 2025)
The study aims to comparative analysis of employee engagement employees across generations of PT X. This study uses simple random sampling techniques because PT X employees numbered 61 people.The results showed that all employee engagement indicators based on Q12 (Gallup) in PT X were included in the engaged category. Employee engagement in PT X is included in the engaged category in accordance with the efforts made by the company to maintain/improve employee engagement.